Problems and prospects for development of institutional investors' activities on the financial market of Ukraine - FEDOROVYCH, Iryna (Scientific journal «World of Finance», 2019)
Introduction. Institutional investors play an important role in the economy. They perform efficient redistribution of resources and reduce the risk in conditions of uncertainty, take a part in the transformation of savings-investment. Activity of institutional investors give the opportunity reduce the speculative component of the domestic financial market by means of giving to human instruments of pension fund scheme and accumulation of savings, that has an positive impact on level of the human wellbeing.Purpose - analysis of features of the activities of different types of institutional investors’ development in the domestic financial market and developing of proposals which are aimed at improving of the regulation of their activities.Results. The level of activity of institutional investors in Ukraine is still low because of the poorly developed system of attracting of household savings into the stock market, which is not ensured the flow of funds into the economy; institutional investors are not competitive in the stock market; pyramid investment scheme are appearing and conditions of the financial security is getting worse. Reducing the number of participants in the asset management asset management company in Ukraine continued in 2016. There were reducing of asset management companies as well as reducing of operative stocks in management and their investors, assets in the management reduced too. In general, results of the year 2016 were mostly positive for investors of Investment fund with public offering, including public foundations and diversified foundations which are oriented on the equity investments, because stock indexes rose mostly during the year. At the same time, unstable regulatory environment, including artificial narrowing of the stock market by administrative methods which prevented to develop activity of institutional investors more active.Conclusion. Development of activities of institutional investors is necessary process in the modern economy. State regulation which is aimed at stimulating of the involvement of public funds, improvement of the legal framework which regulate activities of institutional investors and provides access to a wider range of financial instruments must promote this. The main measures to regulate activity of institutional investors are using of the mandatory electronic document management for institutional investors; introducing amendments to reporting forms which are related investment activities of all types of institutional investors; legal termination of manipulation by price and improvement of legislation on the protection of investors' rights; improvement of tax regulation; creating of favorable conditions for attracting long-term investment resources; enhancing the role of professional self-regulatory organizations and rating agencies on the market of investments; introduction of asset management strategies into practice using the instruments of the derivatives market, if they are used to hedge financial risks; expanding the list of liquid capital markets instruments, including derivatives, in order to provide portfolio diversification and risk management of institutional investors; to ensure the implementation of legislation on the possibility to buy foreign securities by institutional investors; add demands to professionalism of risk managers in the organization of activity of institutional investors.